Prediction of User Loyalty Using the Naive Bayes Method in the "Goprint" Online Printing Marketplace - Widiastawan, Gede; Arya Kadyanan, I Gusti Agung Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 8 No 3 (2020): JELIKU Volume 8 No 3, February 2020DO - 10.24843/JLK.2020.v08.i03.p03, 2020)
Goprint is an Online Printing Marketplace that connects printing services with users who want to print documents quickly without the need to queue. In the span of time from April 2019 to September 2019 it was found that the number of Goprint users reached 407 users, 24 partners, and 256 orders. From transactions that have been carried out by users, not a few orders are often canceled due to ineffective Goprint features or poor partner performance. This causes Goprint users to feel dissatisfied with the services provided by the Goprint application. The Naive Bayes algorithm is one of the algorithms used for classification or grouping of data, but can also be used for decision making. With this algorithm and the problems that occur, the authors make a system to predict the loyalty of Goprint users to anticipate users who stop leaving Goprint because they are not satisfied or loyal users. The data used as training data is 20 and testing data is 10. From the test results it is found that the value of precision is 80%, 100% recall, and 90% accuracy.